Pengaruh Tampilan Produk UMKM Dibumbuin terhadap Minat Beli Ulang dengan Instagram Marketing sebagai Pemoderasi : Instagram Marketing, Tampilan Produk, Minat Beli Ulang. - Ningrum, Putri Nurlita; Amir, Indra Tjahaja; Atasa, Dita (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2023)
The use of Instagram is a means for not only personal but also business people. Instagram provides features to facilitate the visual aspect seen by its followers. Dibumbuin MSMEs has Instagram but its usage is not maximum. In addition, the income held in the past year has significantly decreased. Even though the product display of existing content is very interesting. The purpose of this study analyzed the effect of product display on repurchase interest with Instagram Marketing as a moderation variable on the Sambal Dibumbuin MSMEs. Methods conducted quantitative research with SEM-PLS analysis. The number of samples used was 68 respondents from consumers. The research results showed that the product display variables and Instagram Marketing for product purchase interest had a significant positive effect on direct relationships of 0.33 and 0.637, respectively. However, the variable Instagram marketing variable cannot be moderated or weakened by the effect of product display on repurchase interest.